2017
DOI: 10.23865/njlr.v3.535
|View full text |Cite
|
Sign up to set email alerts
|

A Shift from Spectator to Creator: A Study of Blog Writing in a Print and Photo High School Class

Abstract: This article is a study of written blog texts from 12 third grade high school students produced during one academic year, commenting on their photos and artwork as part of their curriculum in the discipline Print and Photo. The article aims to capture a change in how the students position themselves as photographers in their blog texts from the beginning towards the end of the academic year. An initial hypothesis is that the students develop a disciplinary language throughout one year of writing about their ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Within the sub-theme writer positions in students' text, ten studies were identified. These studies explored how students position themselves in the text (Dagsland, 2019;Hanghøj et al, 2020;Hultin, 2020;Lyngfelt, 2019;Myklebust, 2017;Nygard, 2017;Ulland et al, 2018 ), and how they experience themselves and/or behave as writers (Hermansson, 2017;Krogh et al, 2015;Nordmark, 2017). For example, Hanghøj et al (2020) investigated how students in years 7-9 (age 13-15) positioned themselves in relation to their everyday experiences with and attitudes towards games when writing a journalistic text within the context of the subject Danish L1.…”
Section: Students' Textsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the sub-theme writer positions in students' text, ten studies were identified. These studies explored how students position themselves in the text (Dagsland, 2019;Hanghøj et al, 2020;Hultin, 2020;Lyngfelt, 2019;Myklebust, 2017;Nygard, 2017;Ulland et al, 2018 ), and how they experience themselves and/or behave as writers (Hermansson, 2017;Krogh et al, 2015;Nordmark, 2017). For example, Hanghøj et al (2020) investigated how students in years 7-9 (age 13-15) positioned themselves in relation to their everyday experiences with and attitudes towards games when writing a journalistic text within the context of the subject Danish L1.…”
Section: Students' Textsmentioning
confidence: 99%
“…In four studies, contextual aspects influencing the students' writing of their texts were investigated (Myklebust & Høisaeter, 2018;Nygard et al, 2017;Rødnes, 2012;Skaar, 2020). Myklebust and Høisaeter (2018) investigated how two different communicative situations influenced the argumentative texts upper secondary students wrote in the subject area Social Studies.…”
Section: Students' Textsmentioning
confidence: 99%